Urban growth and decline in Europe - E.M. Bosker; G.A. Marlet (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2006)
In this paper we examine growth differences between European cities. We have used the Urban Audit, a rather new dataset from Eurostat. After clarifying the merits of this dataset as well as some of its limitations, we provide some detailed characteristics of city growth in the European Union. This shows that urban growth in the EU is pretty persistent and is still, in spite of further European integration, largely driven by growth of national born population; non-national European born and non-European born migrants contribute only marginally to urban growth differentials. Moreover differences in birth rates explain a substantial part of the variation in (national-born population) growth rates. Controlling for these differences in birth rates, we look for the determinants of migration-driven European city growth relative to average city growth in the EU as a whole as well as to average national city growth, meanwhile distinguishing between national, non-national EU and non- EU population growth. Our results suggest that, by and large, the smaller, less dense, safer, amenity-rich cities with high levels of GDP per capita are growing fastest. When focussing on national, EU and non-EU population growth, we moreover find that nationals are attracted to the less dense, amenity-rich, more productive cities; that EU nonnationals are concentrated in cities with high levels of human capital; and that non-EU population growth is determined by climate and by employment structure.
Keywords: 330; European urban growth